Preparation and application of porous titanium carbide loaded copper molybdenum sulfide electrode material

By growing a phosphomolybdate-based copper metal organic frame in situ on the three-dimensional porous MXene surface and preparing Cu2S/MoS2@C/MXene composite material through high-temperature calcination, the problems of unstable catalyst structure and poor conductivity during the electrocatalytic nitrate reduction and synthesis of ammonia were solved, and efficient electrocatalytic performance was achieved.

CN119900049AActive Publication Date: 2025-04-29HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510096707.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the prior art, in the process of electrocatalytic nitrate reduction and synthesis of ammonia, the catalyst structure is unstable and the conductivity is poor, resulting in poor electrocatalytic performance.

Method used

By growing a phosphomolybdate-based copper metal organic frame (NENU-5) in situ on the three-dimensional porous MXene surface, and preparing Cu2S/MoS2@C/MXene composite material by high-temperature calcination, the specific surface area and conductivity of the catalyst are improved by utilizing the synergistic catalytic activity of Cu2S and MoS2.

Benefits of technology

This method effectively improves the performance of electrocatalytic nitrate reduction and synthesis of ammonia, improves catalytic activity and stability, and solves the problems of unstable catalyst structure and poor conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005253050780000011
    Figure HDA0005253050780000011
  • Figure HDA0005253050780000012
    Figure HDA0005253050780000012
  • Figure HDA0005253050780000021
    Figure HDA0005253050780000021
Patent Text Reader

Abstract

The invention relates to preparation of a porous titanium carbide (MXene) loaded copper molybdenum sulfide (Cu2S / MoS2 atC / MXene) electrode material. The obtained composite material is used for synthesizing ammonia through electro-catalysis nitrate radical reduction at normal temperature and normal pressure. The preparation method comprises the following steps: introducing copper ions into layered MXene dispersion liquid through an in-situ growth synthesis method to form MXene hydrogel, taking the MXene hydrogel as a substrate, performing in-situ growth on NENU-5 to obtain an NENU-5 / MXene composite material, and further performing a high-temperature vulcanization process to obtain the Cu2S / MoS2 atC / MXene composite material. The material combines the advantages of Cu2S, MoS2 and MXene, and the stability, the conductivity and the electro-catalytic performance of the catalyst are improved. According to the electrocatalyst prepared by the invention, the yield of synthesis ammonia through reduction of nitrate radicals is 20.24 mg h <-1 > mgcat <-1 >, and the Faraday efficiency is 85.34%. The preparation process is simple and convenient, the cost is low, and the obtained material has good electrocatalytic synthesis ammonia performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst materials for electrocatalytic nitrate reduction ammonia synthesis, and relates to preparation and application of a porous titanium carbide-supported copper-molybdenum sulfide electrode material. Background Art

[0002] Nitrate (NO 3 - ) is a common pollutant in surface water and groundwater. 3 - The accumulation of NO is mainly caused by human activities, such as the burning of fossil fuels, excessive use of nitrogen-rich fertilizers, and wastewater discharge. 3 - The presence of NO may cause eutrophication of water bodies, thereby reducing the oxygen available to aquatic organisms and destroying aquatic ecosystems. 3 - can be reduced to nitrite (NO 2 - ), which can lead to liver damage, methemoglobinemia, and even cancer. Therefore, researchers have tried various methods to reduce NO in water. 3 - The content.

[0003] Electrocatalytic NO 3 - Reduction of ammonia has its unique advantages. First, electrocatalysis of NO 3 - Ammonia, the main product of reduced synthetic ammonia, is the basic raw material for the production of nitrogen fertilizers and fibers, and has high application value. Second, the electricity used in the electrochemical reaction can be obtained from renewable energy. Third, in the electrochemical reaction, electrons act as reducing agents, which neither introduce new impurities nor cause secondary pollution to the environment. However, electrocatalytic NO 3 - Reduction is a complex reaction process involving multiple redox reactions and across multiple valence states. The reduction pathway is rich and accompanied by the generation of many intermediates and by-products. Therefore, it is important to explore electrode materials with excellent catalytic activity for electrocatalytic NO reduction. 3 - Research focus on reducing synthetic ammonia.

[0004] Transition metal carbon / nitrogen / carbon nitride (MXene) materials have been widely used in energy storage, sensing, catalysis, biology and other fields due to their unique morphology, metal-like conductivity and high chemical stability. 2 Molybdenum disulfide (MoS) is a narrow-bandgap p-type semiconductor material with good chemical and thermal stability and is a good conductive material. 2) is composed of three atomic layers, with a molybdenum atomic layer sandwiched between two sulfur atomic layers, forming a special layered morphology similar to a "sandwich" structure, so it has excellent anisotropy and electrocatalytic properties.

[0005] Polyoxometalates (POMs, referred to as polyoxometalates) are constructed by introducing polyoxometalates (POMs, referred to as polyoxometalates) as guest molecules into the main body of the metal organic framework (MOF). It not only retains the excellent physical and chemical properties of POMs, but also the high porosity of MOF provides a platform for the good dispersion of POMs. Using POMOFs as a precursor, a multi-component metal composite material with a heterogeneous structure interface can be prepared. The present invention uses a phosphorus molybdenum polyoxometalate-based copper metal organic framework (NENU-5) composite material (abbreviated as NENU-5@MXene) in situ grown on the surface of a three-dimensional porous MXene as a precursor, and further obtains a three-dimensional porous MXene-supported copper molybdenum sulfide composite material (Cu 2 S / MoS 2 @C / MXene) and applied it to electrocatalysis of NO 3 - Reduction of synthetic ammonia is a task with good application prospects and research significance. Summary of the invention

[0006] The purpose of the present invention is to in situ grow a phosphomolybdic acid-based copper metal organic framework (NENU-5) on a three-dimensional porous structure MXene to synthesize a NENU-5 / MXene composite material, and further prepare a Cu by high-temperature calcination in a tubular furnace. 2 S / MoS 2 @C / MXene composites. Cu with synergistic catalytic activity 2 S and MoS 2 In-situ growth on the surface of MXene can prevent the accumulation of MXene nanosheets, increase the specific surface area of ​​the composite material, and maintain the good conductivity and stability of MXene. Using this material as a catalyst can improve the performance of electrocatalytic nitrate reduction to synthesize ammonia.

[0007] In order to achieve the purpose of the above invention, the present invention provides the following technical solutions:

[0008] 1. Preparation of MXene hydrogel: A single layer of MXene was dispersed in deionized water and copper nitrate hexahydrate (Cu(NO 3 ) 2 6H 2 O) is dissolved in deionized water, the two are quickly mixed, and MXene hydrogel is formed within seconds.

[0009] 2. Preparation of NENU-5 / MXene: Solution A, a mixed solution of MXene hydrogel dispersion and trimesic acid; Solution B, copper acetate (Cu(Ac) 2 ·H 2 O) and phosphomolybdic acid (PMo 12 ) mixed solution. Solution A was quickly poured into solution B, fully stirred at room temperature and pressure, washed, centrifuged, and vacuum dried to collect the product NENU-5 / MXene.

[0010] 3.Cu 2 S / MoS 2 @C / MXene composite material preparation: Take a certain amount of NENU-5 / MXene composite material and thiourea in a ratio of 1:20, mix them in a crucible, calcine them at high temperature in a tubular furnace, cool them down, and collect the products.

[0011] 1. The MXene hydrogel dispersion described in step 1, wherein the mass of MXene is 60-65 mg (concentration is

[0012] 10mg / mL), Cu(NO 3 ) 2 6H 2 The mass of O is 60-65 mg (concentration is 0.81 mol / L).

[0013] 2. The mass of the trimesic acid described in step 2 is 0.14-0.15 g, and the solvent is anhydrous ethanol.

[0014] 3. The copper nitrate described in step 2 has a mass of 0.2-0.3 g (concentration of 0.025 mol / L).

[0015] 4. The phosphomolybdic acid described in step 2 has a mass of 0.3-0.4 g.

[0016] 5. The stirring time in step 2 is 30 min, and the mixture is washed several times with anhydrous ethanol and deionized water respectively.

[0017] 6. The mass of the NENU-5 / MXene composite material described in step 3 is 0.2 to 0.3 g.

[0018] 7. The mass of the thiourea described in step 3 is 4 to 5 g.

[0019] 8. The temperature of the tubular furnace described in step 3 is 800°C, the calcination is 2h, and the heating and cooling rates are 7°C / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention can obtain a porous titanium carbide-supported copper-molybdenum sulfide electrode material Cu2 S / MoS 2 @C / MXene. The three-dimensional porous MXene has a larger specific surface area, which effectively avoids the re-stacking of MXene two-dimensional nanosheets and is more conducive to the loading of catalytic active substances. At the same time, the functional groups on the surface of MXene have certain reactivity and electronegativity, which promotes the deprotonation of organic ligands as strong electron donors, so that NENU-5 can be nucleated in situ on the surface of MXene to obtain NENU-5 / MXene, and then further calcined at high temperature to finally synthesize Cu 2 S / MoS 2 @C / MXene composite material. Cu 2 S and MoS 2 It is evenly dispersed on the porous MXene surface, solving the problems of unstable catalyst structure and poor conductivity. This material is used for electrocatalytic nitrate reduction to synthesize ammonia, and the electrocatalytic performance is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @Comparison chart of Fourier transform infrared spectra (FT-IR) of C / MXene composite materials.

[0023] Figure 2 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @Scanning electron microscope (SEM) image of C / MXene composite material.

[0024] Figure 3 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composite powder X-ray diffraction (XRD) pattern.

[0025] Figure 4 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composites with or without NO 3 - Current-potential (LSV) curves in electrolyte.

[0026] Figure 5 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composites in neutral electrolyte (0.1 mol / LNa 2 SO 4 and 0.1 mol / LNaNO3 ) was used to carry out nitrate reduction to synthesize ammonia, and the ultraviolet-visible absorption spectra (UV-vis) of the electrolytes obtained after 1 hour of testing at different voltages were measured.

[0027] Figure 6 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composites in neutral electrolyte (0.1 mol / LNa 2 SO 4 and 0.1 mol / LNaNO 3 ) was used to carry out the nitrate reduction reaction to synthesize ammonia, and the ammonia yield and Faraday efficiency diagram after 1 hour of testing at different voltages. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with implementation and comparative examples and drawings, but the embodiments of the present invention are not limited thereto.

[0029] Implementation Case 1

[0030] This embodiment provides a Cu 2 S / MoS 2 @C / MXene composite electrocatalyst, which is prepared according to the following method:

[0031] Preparation of MXene hydrogel: Disperse a single layer of MXene in deionized water and add Cu(NO 3 ) 2 6H 2 O is dissolved in deionized water, the two are quickly mixed, and the MXene hydrogel is formed within seconds.

[0032] Preparation of NENU-5 / MXene: Solution A, a mixed solution of MXene hydrogel dispersion and trimesic acid; Solution B, Cu(Ac) 2 ·H 2 O and PMo 12 Pour solution A into solution B quickly, stir thoroughly at room temperature and pressure, wash, centrifuge, vacuum dry, and collect the product.

[0033] Cu 2 S / MoS 2 @C / MXene composite material preparation: Take a certain amount of NENU-5 / MXene composite material and thiourea in a ratio of 1:20, mix them in a crucible, calcine them at high temperature in a tubular furnace, cool them down, and collect the products.

[0034] Comparative Case 1

[0035] This comparative case provides a Cu 2 The S@C / MXene composite electrocatalyst is different from Example 1 in that PMo is not added to Solution B in Step 2. 12 .

[0036] Comparative Case 2

[0037] This comparative case provides a MoS 2 @C / MXene composite electrocatalyst, the difference from Example 1 is that no Cu(Ac) is added to solution B in step 2 2 ·H 2 O.

[0038] The present invention will be further described below in conjunction with the accompanying drawings:

[0039] Figure 1 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 Comparison of Fourier transform infrared spectra of @C / MXene composite materials. As shown in the figure, at 1571-1673cm -1 In the range of 2.5 Å, weak broad peaks can be observed, which are attributed to the vibrations of ν(CC) and ν(CH) generated in the carbon layer formed after the organic ligands in NENU-5 / MXene are calcined, and there is an obvious Cu 2 S@C / MXene and MoS 2 @C / MXene infrared characteristic peaks indicate that both are successfully loaded on MXene.

[0040] Figure 2 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composite scanning electron microscope image. As shown in Figure a, it can be observed that the surface of the base MXene is rough and has an obvious three-dimensional porous structure; Figures b and c show that there are nanoparticle structures distributed on the surface of MXene, indicating that Cu 2 S and MoS 2 Successfully loaded onto three-dimensional porous MXene.

[0041] Figure 3 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composite powder X-ray diffraction diagram. As shown in the figure, the 2θ peaks at 27.4°, 31.7°, 45.5°, and 53.9° are respectively attributed to Cu 2 The (111), (200), (220), and (311) crystal planes of S are consistent with Cu 2S standard card (JCPDS NO.84-1770); the 2θ peaks at 14.1°, 32.9°, 35.9°, 43.3°, and 69.1° are respectively attributed to MoS 2 The (002), (100), (102), (006), and (200) crystal planes are consistent with MoS 2 Standard card (JCPDS NO.75-1539); and Cu 2 S / MoS 2 @C / MXene composites have characteristic peaks of MXene, indicating that Cu 2 S and MoS 2 Successfully loaded on MXene, Cu 2 S / MoS 2 @C / MXene composite materials were successfully synthesized.

[0042] Figure 4 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composites with or without NO 3 - Electrochemical linear sweep voltammogram in electrolyte. As shown in the figure, in the voltage range of -1.1V vs.RHE to -1.5V vs.RHE, Cu 2 S / MoS 2 The reduction current density of the @C / MXene composite material in the electrolyte containing nitrate ions is significantly higher than that in the electrolyte without nitrate ions, indicating that the Cu 2 S / MoS 2 @C / MXene composite materials have certain electrocatalytic nitrate reduction ability.

[0043] Figure 5 The Cu prepared in Example 1 of the present invention 2 S / MoS 2 @C / MXene composites in neutral electrolyte (0.1 mol / LNa 2 SO 4 and 0.1 mol / LNaNO 3 ) was used to perform a nitrate reduction reaction to synthesize ammonia, and the UV-visible absorption spectra of the electrolytes obtained after 1 hour of testing at different voltages were measured. As shown in the figure, as the applied voltage increases, the absorbance of the electrolytes that were color-developed after the electrocatalytic test in the absorbance test also gradually increases.

[0044] Figure 6 The Cu prepared in Example 1 of the present invention 2 S / MoS 2@C / MXene composites in neutral electrolyte (0.1 mol / LNa 2 SO 4 and 0.1 mol / LNaNO 3 ) was used to synthesize ammonia by nitrate reduction reaction, and the ammonia production and Faraday efficiency after 1 h of testing at different voltages were plotted. As shown in the figure, at a potential of -1.3 V vs. RHE, the highest Faraday efficiency was 85.34%, and the corresponding ammonia production was 20.24 mg h –1 mg cat. 1 Therefore, Cu 2 S / MoS 2 @C / MXene composites can be used as an efficient electrocatalytic nitrate reduction catalyst for ammonia synthesis.

[0045] In summary: Cu of implementation case 1 2 S / MoS 2 @C / MXene composite material was successfully prepared by the synthesis method of room temperature stirring and high temperature calcination, and was successfully applied to the electrocatalytic nitrate reduction to synthesize ammonia. The addition of MXene increased the specific surface area and electron transfer rate of the composite material. 2 S and MoS 2 The synergistic catalytic effect of the two improves the electrocatalytic activity. The material has good redox activity, excellent conductivity and electrocatalytic stability, and has great potential in the electrocatalytic reduction of nitrates to synthesize ammonia.

Claims

1. Preparation and application of a porous titanium carbide-supported copper-molybdenum sulfide electrode material, characterized in that: (1) Preparation of MXene hydrogel: A single layer of MXene is dispersed in deionized water, and copper nitrate hexahydrate (Cu(NO3)2·6H2O) is dissolved in deionized water. The two are quickly mixed, and MXene hydrogel is formed within a few seconds. (2) Preparation of NENU-5 / MXene: Solution A, a mixed solution of MXene hydrogel dispersion and trimesic acid; Solution B, copper acetate (Cu(Ac)2·H2O) and phosphomolybdic acid (PMo 12 ) mixed solution. Solution A was quickly poured into solution B, fully stirred at room temperature and pressure, washed, centrifuged, freeze-dried, and the product NENU-5 / MXene was collected. (3) Preparation of Cu2S / MoS2@C / MXene composite material: Take a certain amount of NENU-5 / MXene composite material and thiourea in a ratio of 1:20, mix them in a crucible, calcine them at high temperature in a tubular furnace, cool them down, and collect the products.

2. The MXene hydrogel dispersion according to step (1) of claim 1, wherein the mass of MXene is 60 to 65 mg (concentration is 10 mg / mL), and the mass of Cu(NO3)2·6H2O is 60 to 65 mg (concentration is 0.81 mol / L).

3. According to the trimesic acid described in step (2) of claim 1, its mass is 0.14-0.15g, and the solvent is anhydrous ethanol.

4. The Cu(Ac)2·H2O according to step (2) of claim 1, wherein the mass of the Cu(Ac)2·H2O is 0.2-0.3 g (the concentration is 0.025 mol / L).

5. The PMo according to step (2) of claim 1 12 , its mass is 0.3~0.4g.

6. According to claim 1, the stirring time in step (2) is 30 min, and the mixture is washed several times with anhydrous ethanol and deionized water respectively.

7. The NENU-5 / MXene composite material according to step (3) of claim 1, having a mass of 0.2 to 0.3 g.

8. The thiourea according to step (3) of claim 1, having a mass of 4 to 5 g.

9. According to step (3) of claim 1, the temperature of the tubular furnace is 800°C, the calcination is 2h, and the heating and cooling rates are 7°C / min.

10. The Cu2S / MoS2@C / MXene composite material prepared by the method for preparing the composite material according to claims 1 to 9 is used for electrocatalytic nitrate reduction to synthesize ammonia at room temperature and pressure.

Citation Information

Patent Citations

  • Preparation of Ti3C2Tx / NENU-3 composite material and application of Ti3C2Tx / NENU-3 composite material in electrocatalytic synthesis of ammonia

    CN118880375A

  • Phosphorus-doped cose 2 / mxene composite material and preparation method therefor

    WO2022032751A1